Inhibitors Against Glycosidases as Medicines - Kajimoto, Tetsuya; Node, Manabu (Current Topics in Medicinal Chemistry, 2009)
Glycosidases mediate the digestion of oligosaccharides in the small intestine as well as the processing of cell surface oligosaccharides, which play important roles in cell to cell recognition during infections, metastasis, and immune responses. Thus, agents that control the activities of glycosidases could have therapeutic effects against many carbohydrate-related diseases. In fact, many fruitful efforts have been made to design and synthesize glycosidase inhibitors as clinically practical medicines. This review summarizes the current stage of development of such inhibitors to treat diabetes, influenza, virus infection of HIV, tumor metastasis, and glycosyl sphingo lipid (GSL) storage diseases.
Keywords: carbohydrate-related diseases